Analisis Kebutuhan Pengguna pada Pengembangan Malang Virtual Tourism dengan Ambience Lingkungan Terintegrasi - Wardhono, Wibisono Sukmo; Tolle, Herman; Dewi, Ratih Kartika; Fanani, Lutfi (Proceedings Series on Physical & Formal Sciences, 2023)
The use of VR in the tourism business continues to increase. The use of VR for tourism is known as virtual tourism. virtual tourism can simulate tourist destinations using a virtual environment (VE). Virtual tourism is expected to enhance the experience for tourists and attract new markets to tourist destinations. Malang City is one of the tourist destinations in East Java, and is always visited by both domestic and foreign tourists. However, Malang City is still not a major destination in tourism, compared to Batu City (Kota Batu) and Malang Regency (Kabupaten Malang), this is due to the lack of vigorous promotion. In order to provide a pleasant experience for its users, Malang Virtual Tourism must be developed based on user needs. Based on these problems, a virtual reality application will be developed that can provide immersive experiences to users related to tourist destinations in Malang City. At the requirement analysis stage, a specification design of the system to be made includes functional and non-functional requirements needed for the development of the system in this research will be carried out. The requirement analysis process involves potential users of the system. We were identifying the requirements by numbering each requirement that has been made with a Use case diagram and Use case Scenario. This step generates a general description and system requirements. The results of this stage get five functional requirements and one non-functional, usability.